Teacher Vocational Education Competence in Digital Age: A Bibliometric Analysis - Kurnia Santi; Iwan Kustiawan (Universitas Ahmad Dahlan, 2023)
Over the years technology has transformed the way people live and behave. Teaching clearly cannot be an exception. Teachers at all levels of education undergo a process of adaptation to develop the digital skills necessary for this transformation. Moreover, vocational education teachers are required to adapt the skills taught to the needs of the industry. The purpose of this paper is to provide an extensive bibliometric literature review on the competence of vocational education teachers in the digitalization era. Articles are found via publish or perish software and the Google Scholar database. Scanning by scimagojr.com (Q1, Q2, Q3, and Q4), we analyzed 42 articles from 26 leading journals from January 1, 2010 to June 30, 2022. Mendeley software is used to manage and resume references. We have reviewed this database and tried to classify articles using the VOSviewer software. Three groups were reviewed; The words that appear most often in each group are ‘vocational education’, ‘apprentices’, teaching’, ‘e-learning’, professioanl competence’, dan ‘competence based education’ This cluster represents the flow of teacher digital competence (TDC) research.